Emergency Contraception in Post‐Conflict Somalia: An Assessment of Awareness and Perceptions of Need. Issue 1 (March 2016) - Gure, Faduma; Dahir, Mohammed Koshin; Yusuf, Marian; Foster, Angel M.
Abstract : In conflict‐affected settings such as Somalia, emergency contraception (EC) has the potential to serve as an important means of pregnancy prevention. Yet Somalia remains one of the few countries without a registered progestin‐only EC pill. In 2014, we conducted a qualitative, multi‐methods study in Mogadishu to explore awareness of and perceptions of need for EC. Our project included 10 semi‐structured key informant interviews, 20 structured in‐person interviews with pharmacists, and four focus group discussions with married and unmarried Somali women. Our findings reveal a widespread lack of knowledge of both existing family planning methods and EC. However, once we described EC, participants expressed enthusiasm for expanding access to post‐coital contraception. Our results shed light on why Somalia continues to be a global exception with respect to an EC product and suggest possible politically and culturally acceptable and effective avenues for introducing EC into the health system.